Marketing Optimization of Kerupuk Melarat and Opak Beca Through E-Commerce Learning - Vicky Silva Rahmah; Refaldo Fanther (Cirebon International Journal of Economics and Business, 2023)
E-Commerce can be a great opportunity for MSME players to develop their business and allow them to do marketing with the aim of global markets, so that they have the opportunity to penetrate exports. The large increase in the E-Commerce business shows the many advantages it offers. Astapada Village it self, the majority of its residents are MSME actors who focus on food, namely Kerupuk Melarat and Opak Beca, both of which are the hallmarks of the village. However, in terms of online marketing, it has not been optimally carried out due to several factors that become obstacles. This research method uses the Participatory Action Research (PAR) method with a problem tree technique and a ranking matrix or priority scale (ranking). Motivation to move forward and a strong will is the first step that every MSME actor needs to develop and improve his business.